From governance to choreography: coordination of innovation ecosystems - Diego Alex Gazaro dos Santos; Aurora Carneiro Zen; Bruno Anicet Bittencourt (Innovation & Management Review, 2022)
Purpose - Innovation ecosystems can emerge and grow organically, but the process can also be managed through conscious intervention. Therefore, this study observes different motivations and expectations for each group of actors. The lack of alignment between actors could have a negative influence on the development of innovation ecosystems. This study aims to analyze the coordination strategies of the actors throughout the life cycle of innovation ecosystems. Design/methodology/approach - This study develops and proposes a model for coordinating innovation ecosystems based on the theoretical backgrounds of the ecosystem life cycle and ecosystem coordination. Findings - This study argues that each stage of an innovation ecosystem's life cycle - inception, launching, growth and maturity - demands different coordination strategies. Initially, networks are simpler and thus the coordination issues are less difficult. However, as the ecosystem evolves and the complexity of the networks increases, a more sophisticated strategy, such as orchestration or choreography, is needed. Research limitations/implications - This is a theoretical study that recommends further research to test this model. Practical implications - The understanding of coordination and stages of the life cycle of an innovation ecosystem can guide actors in the design of strategies for developing of ecosystems. Social implications - The proposed framework could support strategies to engage civil society in actions to develop innovation ecosystems. Originality/value - This study presents a framework to understand the coordination strategies better, considering the stages of an innovation ecosystem's life cycle.
Keywords: 650; Ecosystem coordination; Ecosystem life cycle; Innovation ecosystem